Antecedent factors influencing maternal health information seeking behaviour of women of childbearing age in rural Tanzania - Kassim, Mohamed; Katunzi-Mollel, Kokuberwa (University of Dar es Salaam Library Journal, 2021)
Seeking maternal health information from relevant and reliable sources is essential in reducing pregnancy-related complications that may result in both maternal morbidity and mortality. This study has investigated factors that influence maternal health information seeking behaviour of women of childbearing age in rural Tanzania. The study utilized a descriptive research design combining quantitative and qualitative research approaches. The study has used questionnaires, administered to 380 respondents, and focus group discussions involving 29 participants to collect data. Findings indicate that several factors are responsible for the women ' s information seeking behaviour. These factors are: proximity to information sources; economic factors; previous pregnancy experiences; direct experience with information sources; information sources ' ability to provide relevant and adequate health information and women ' s belief that the sought information will help to address their health problems. This study concludes that health practitioners and maternal health information providers should be mindful of these factors when providing maternal health information to women in rural areas. Furthermore, while it is important to encourage women to seek health information from reliable sources, it is also essential to equip them with information literacy skills to enable them to evaluate the health information they receive from their social networks and other informal sources.